2000
DOI: 10.1159/000053253
|View full text |Cite
|
Sign up to set email alerts
|

Height, Bone Mineral Density and Bone Markers in Congenital Adrenal Hyperplasia

Abstract: Aim: To evaluate height, bone growth, areal bone mineral density (aBMD), volumetric bone mineral density (vBMD) and markers of bone turnover in a group of patients affected by congenital adrenal hyperplasia (CAH). Patients: There were 50 patients (23 males, 27 females), aged 1–28 years, affected by CAH due to 21-hydroxylase deficiency: 27 with the salt-wasting (SW); 14 with the simple virilizing (SV), and 9 with the nonclassical (NC) forms. Methods: Bone morphometry was evaluated with the metacarpal index (MI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 18 publications
3
52
1
1
Order By: Relevance
“…The majority of studies have found normal bone density in both children and young adults with CAH [18][19][20][21][22] . However, some data indicate skeletal deficits 23 . Bone mineral density and bone mineral content in our participants were normal and did not correlate with current glucocorticoid dose or androgen levels.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have found normal bone density in both children and young adults with CAH [18][19][20][21][22] . However, some data indicate skeletal deficits 23 . Bone mineral density and bone mineral content in our participants were normal and did not correlate with current glucocorticoid dose or androgen levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that osteoporosis risk is higher in adult patients with CAH compared to the normal population (6)(7)(8)(9). However, in younger CAH patients there are contradictory results in published studies and case reports that reported that BMD values were not changed or decreased (10)(11)(12)(13)(14)(15)(16)(17)(18). This situation may be related to smaller numbers of patients, extensive range of age distribution, and heterogeneous glucocorticoid dose among groups.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have reported increased BMI in 21OHD patients (7,8), but not in all (9), and some studies have reported increased fat mass (7,8,9). Glucocorticoid therapy may also reduce bone mineral density (BMD), whereas androgens increase BMD in men (10), and studies have shown reduced (11), normal (12) and increased BMD (13) in 21OHD patients. Little is known about the risk of cardiovascular and other metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%